High Nuclearity Cu(II) and Co(II) complexes of Schiff Base Derived from o-vanillin with substituted m-phenylenediamine - Solihah Khaidir, Siti; Bahron, Hadariah; Mohd Tajuddin, Amalina; Ramasamy, Kalavathy; Meng Lim, Siong (International Journal of Engineering and Technology, 2018)
In the present work, a polydentate Schiff base ligand (SB) was synthesized via condensation reaction between o-vanillin and Cl-m-phenylenediamine. Dinuclear complexes of Co(II) and Cu(II) were prepared by conventional method with SB:metal ratio of 1:1 whereas tetranuclear complexes were obtained via microwave-assisted synthesis with SB:metal ratio of 1:2. Characterization was carried out through elemental analysis (C,H,N), molar conductivity, magnetic susceptibility, Fourier Transform Infrared (FTIR), and Nuclear Magnetic Resonance (NMR) spectroscopy. The experimental data indicated that the metal ions of the dinuclear and tetranuclear complexes were coordinated to the ligand through azomethine nitrogen, methoxy oxygen and deprotonated phenolic oxygen. The effective magnetic moment values of Co(II) complexes suggested tetrahedral geometry with 3 unpaired electrons. The shifting of n(C=N), n(C-O)phenolic and n(C-O)methoxy band to lower frequencies in all complexes indicated that coordination to metal centres occurred through these moieties. New weak peaks in the region 436 -559 cm-1 were assignable to n(M-N) and n(M-O). SB and its complexes were screened to be positive for anticancer activities against human colon cancer cell (HCT116). Tetranuclear Cu4SB and Co4SB metal complexes revealed IC50 values of 4.2 and 6.87, respectively; indicated to be more potent anticancer agents than the dinuclear counterparts and the parent ligand.Â  Â